Prevalence of pterygium in a tertiary hospital in North-Western Nigeria - Fasasi, M K; Azonobi, I R; Olatunji, F O; Saka, E S (Journal of Chitwan Medical College, 2017)
Pterygium is a wing shaped conjunctival growth that encroaches onto the cornea. It was initially believed to be a conjunctival degeneration arising from pinquecula. However, it is now believed to be an active invasive inflammatory process leading to fibrovascular proliferation. The ocular symptoms of pterygium includes: tearing, redness, foreign body sensation and blurring of vision. Treatment option includes use of steroid and non-steroidal anti-inflammatory drug and various surgical options. A retrospective study was conducted from 1st January 2014- 31st December 2014. Folders of patients seen over this period were retrieved and reviewed. The following information were extracted; socio-demographics (age, gender, occupation, tribe), complaints, visual acuity at presentation, grade of pterygium, treatment offered, history of pterygium surgery, laterality and use of antimetabolities during surgery. The data was recorded and analysed using SPPS version 18. Out of 2760 patients, 98 patients presented with pterygium with a prevalence of 3.6%. Among these, 60.2% were males and 39.8% were females with a range of 22years-73 years (mean 40.28 ± 11.78years). Majority of the patients (31.6%) were between 30years to 39years. Most of the patients were house wives (31.6%) and Hausa (79.6%) by tribe. Most of them had bi-lateral pterygium (66.5%). Majority of the pterygium (46.9%) were of grade 1 followed by 39.8% grade 2. Only 9.2% had surgical procedure and intraoperative application of 5 Fulourouracil (5FU). Three out of 9 cases operated had recurrent pterygium. The prevalence of pterygium is low in this population, majority of cases affecting young and middle age population.